Foreign Direct Investment and Growth Relationship in Georgia - Faruk Gürsoy; Huseyin KALYONCU (International Journal of Economics and Financial Issues, 2012)
This paper aims to investigate the empirically the impact of FDI on economic growth of Georgia over the period of 1997-2010. The Engle-Granger cointegration and Granger causality tests are used in order to analyse the causal relationship between FDI and economic growth. It is crucial to see the directions of causality between two variables for the policy makers to encourage private sectors. It is found that these two variables are cointegrated. Our empirical findings suggest that it is FDI that causes GDP in the case of Georgia.